Activation of Aromatic C−C Bonds of 2, 2'‐Bipyridine Ligands. Issue 48 (14th October 2016) - Fombona, Sergio; Espinal‐Viguri, Maialen; Huertos, Miguel A.; Díaz, Jesús; López, Ramón; Menéndez, M. Isabel; Pérez, Julio; Riera, Lucía
Abstract: 4, 4'‐Disubstituted‐2, 2′‐bipyridine ligands coordinated to Mo II and Re I cationic fragments become dearomatized by an intramolecular nucleophilic attack from a deprotonated N ‐alkylimidazole ligand in cis disposition. The subsequent protonation of these neutral complexes takes place on a pyridine carbon atom rather than at nitrogen, weakening an aromatic C−C bond and affording a dihydropyridyl moiety. Computational calculations allowed for the rationalization of the formation of the experimentally obtained products over other plausible alternatives. Abstract : Dearomatized pyridyl moieties resulting from an intramolecular nucleophilic attack react preferentially (with HOTf) through an aromatic C−C bond rather than through the already activated C−N bond. As a consequence, a pyridyl ring of a 2, 2'‐bipyridine ligand (one of the most widely used ligands, considered remarkably inert) is transformed into a dihydropyridyl group with the result of a weakening of an aromatic C−C bond.